Masa Depan Pendidikan Multikultural di Era Digital - Yusnaldi, Eka; Nabila, Putri; Hasibuan, Najwa Naumira; Salsabila, Maya; Hasibuan, Salsa Bila; Pebri, Mitta (LPPM STAI Ihyaul Ulum Gresik, 2021)
Multicultural education plays a fundamental role in building an inclusive society that values diversity. In the digital era, multicultural education is undergoing a significant transformation due to technological advances and the process of globalization. This research examines the future prospects of multicultural education in the digital context, focusing on the opportunities and challenges. The results show that digital technology offers great opportunities to expand access and improve the quality of multicultural education through online learning platforms, social media and interactive digital tools that encourage intercultural interaction. However, a number of challenges need to be addressed, including the digital divide, protection of privacy and data security, and quality control of educational content. With the right strategies, the digital age can catalyze multicultural education, strengthen cross-cultural understanding, and promote tolerance and global cooperation. This research provides recommendations for inclusive and adaptive educational policies and practices to maximize the benefits of the digital age in supporting more effective and holistic multicultural education.